Treatment satisfaction in patients with relapsing-remitting multiple sclerosis initiated on teriflunomide in routine clinical practice: Australian observational data. Issue 2 (4th July 2022) - Hardy, Todd A; Parratt, John; Beadnall, Heidi; Blum, Stefan; Macdonell, Richard; Beran, Roy G; Shuey, Neil; Lee, Andrew; Carroll, William; Shaw, Cameron; Worrell, Richard; Moody, Jana; et al.
Abstract : Background: Adherence and persistence are critical to optimising therapeutic benefit from disease-modifying therapies (DMTs) in relapsing-remitting multiple sclerosis (RRMS). This prospective, open-label, multicentre, observational study (AubPRO), conducted in 13 hospital-based neurology clinics around Australia, describes treatment satisfaction in patients newly initiated on teriflunomide (Aubagio) and evaluates the use of an electronic patient-reported outcome (PRO) tool. Methods: Patients (≥18 years) newly initiated on teriflunomide (14 mg/day) were followed up at 24 and 48 weeks. Patients completed questionnaires and pill counts electronically using MObile Data in Multiple Sclerosis. The primary endpoint was treatment satisfaction, measured by the Treatment Satisfaction Questionnaire for Medication (TSQM, V.1.4), at week 48. Secondary endpoints included treatment satisfaction at week 24, other PRO scales, clinical outcomes, medication adherence and safety. Results: Patients (n=103; 54 (52.4%) treatment naive) were mostly female (n=82 (79.6%)), aged 49.5 (11.8) years, with MS duration since symptom onset of 9.1 (11.8) years and a median Expanded Disability Status Scale score of 1.0. Mean treatment satisfaction scores were high (≥60%) across all domains of the TSQM V.1.4 at week 24 and at week 48. Compared with week 24, week 48 treatment satisfaction increased for patients who were treatment naïve and for those previously on another oral or injectable DMT. Over 48 weeks, PROs remained stable across a range of measures including disability, physical health, emotional health and mobility, and there were improvements in work capacity and daily life activity. Adherence was high throughout the study with mean compliance (pill counts) of 93.2%±6.26%, and 98 of 103 (95.1%) patients remained relapse-free. Conclusion: This cohort of Australian patients with RRMS, newly initiated on teriflunomide, and treated in a real-world clinical practice setting, reported high treatment satisfaction and adherence at 24 and 48 weeks. Patient-reported measures of disability remained stably low, work capacity and daily life activity improved, and most patients remained relapse-free.